Digital Marketing Strategy Based on Market Penetration and Focused Differentiation in a Warehousing Services Startup: A Case Study of Secure Stash - Windy Aristin; Rhian Indradewa; Hamdi Hamdi; Muhammad Dhafi Iskandar (Efektor, 2026)
This study aims to analyze the marketing strategies implemented by Secure Stash, a startup in the warehousing services sector. In facing an increasingly competitive and dynamic market, the company adopts a combined approach of market penetration and focused differentiation strategies. Market penetration is carried out through the utilization of digital marketing tools such as social media, websites, and partnerships with MSMEs to expand consumer reach. Meanwhile, differentiation is achieved by providing technology-based warehousing services, including the use of IoT, data security, and premium customer service. This research employs a qualitative descriptive approach with a case study method. Data were obtained from the company’s internal documents and supported by recent scholarly literature. The analytical tools used include SWOT, IE Matrix, and QSPM to determine the most relevant and effective core strategies. The findings indicate that market penetration is more suitable during the company’s early growth phase, while differentiation focus serves as the main source of long-term competitive advantage. These results reinforce the view that well-structured, technology-driven digital marketing strategies can enhance customer acquisition, strengthen brand positioning, and build customer loyalty in the logistics and warehousing services sector. Secure Stash demonstrates that startups can compete in traditional industries through service innovation and the appropriate use of digital strategies.